Sinergitas Sekolah Dan Keluarga: Optimalisasi Pembinaan Akhlak Mulia Siswa SMA - Nurhaliza Rizki Avrilla; Azhar Ghaida Kurniawan; Berliani Ninta Tribrata; Raissa Vera Ivanna; Sylvi Nur Aisyah; Muhamad Parhan (Jurnal Wanita dan Keluarga, 2023)
Islamic religious education is important for every Muslim individual to be a guide to life, starting from the family environment and then continuing to the school environment to be an important factor that needs attention. However, during this era of globalization, differences in morality, opinions, and abilities arise. Therefore, the scope of the school or family requires an innovative teaching system that is suitable for this era. By using mixed methods research through reading materials and questionnaires that have been distributed, the result obtained is that the majority of students feel that they have received a fairly good religious education, but some have not for several reasons. Teachers or parents must adjust and know the latest news in the digital era, besides that teachers or parents are prohibited from 'locking' students in an isolated environment away from digital media. Optimizing noble morals in students is influenced by two factors, namely internal factors desired by the students themselves and external factors desired by the family, school, or community. The importance of the contribution between children, schools, and families is the main factor so that every child is not affected by the negative globalization that is rampant today.